Diagnosis, Clinical Characteristics, and Treatment Modalities of Adolescent May-Thurner Syndrome–associated Deep Venous Thrombosis. Issue 3 (April 2021) - Cohen, Clay T.; Kirk, Susan; Desai, Sudhen B.; Kukreja, Kamlesh U.; Srivaths, Lakshmi
Abstract : May-Thurner syndrome (MTS) predisposes individuals to develop lower extremity deep venous thrombosis (DVT) because of compression of the left common iliac vein. Diagnosis of the anatomic obstruction is critical for effective therapy, as treatment by interventional radiology is often required in addition to anticoagulation to prevent thrombus progression and recurrence. The authors performed a retrospective review of adolescent patients who presented with MTS-associated DVT at a pediatric tertiary care center from 2009 to 2018 to assess for delays in MTS diagnosis after the presentation. Fourteen patients (median age 16.5 y, range, 13.8 to 17.9 y) were included, no DVTs were provoked by a central venous catheter. The median time from DVT to MTS diagnosis was 0.65 months (range, 0 to 21.5 mo). The initial imaging modalities used for DVT diagnosis were not able to diagnosis MTS. All patients were treated with anticoagulation and 13 underwent interventional therapy. Four patients had thrombus progression or recurrence, whereas 6 had complete thrombus resolution on follow-up imaging. Three patients who had a delayed MTS diagnosis had clinical worsening despite therapeutic anticoagulation requiring rehospitalization. Adolescent patients with "unprovoked" left lower extremity DVT should undergo appropriate imaging to diagnose MTS to allow for adequate medical and interventional therapy.